2019
DOI: 10.24052/jbrmr/v14is01/art-01
|View full text |Cite
|
Sign up to set email alerts
|

Organisational factors influencing the application of age management

Abstract: There are currently significant differences in the approach to various age groups in many fields of human activity. Due to the global demographic trend of an increasing age of population and growing number of people in the 50+ category, it is necessary to adopt measures that take age into account on the social level and also in the process of organisational management; these measures are collectively referred to as age management. The aim of this paper is to identify and evaluate factors on the organisational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Urbancova and Fajcikova (2019) concluded that significant variations in age exist in various fields of study. Being older is perceived as a positive differentiator.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Urbancova and Fajcikova (2019) concluded that significant variations in age exist in various fields of study. Being older is perceived as a positive differentiator.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the global demographic trend of increasing the age of the population and the growing number of people in the 50+ category, it is necessary to adopt measures that take age into account on the social level and also in the process of organizational management. These measures are collectively referred to as age management [13].…”
Section: Aging Population and Age Diversity Of The Workforcementioning
confidence: 99%
“…Such organizations can respond to the needs of the internal and external environment. In both environments they are transparent and they adapt to changes in demographic development [13].…”
Section: Motivation In the Context Of Age Managementmentioning
confidence: 99%